2012
DOI: 10.1159/000337760
|View full text |Cite
|
Sign up to set email alerts
|

Eye Shape and Retinal Topography in Owls (Aves: Strigiformes)

Abstract: The eyes of vertebrates show adaptations to the visual environments in which they evolve. For example, eye shape is associated with activity pattern, while retinal topography is related to the symmetry or ‘openness’ of the habitat of a species. Although these relationships are well documented in many vertebrates including birds, the extent to which they hold true for species within the same avian order is not well understood. Owls (Strigiformes) represent an ideal group for the study of interspecific variation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
91
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(98 citation statements)
references
References 187 publications
(234 reference statements)
4
91
1
1
Order By: Relevance
“…Some precedent for the existence of such long-lasting phylogenetic effects is provided by the existence of 'nocturnal' eye shapes in other diurnal amniote groups [10]. Some diurnal owls and diurnal geckos retain relatively large corneas compared with diurnal birds and lizards generally [7,9] (but see [51]). Similarly, both owls and geckos probably diversified as predominantly nocturnal radiations [52,53].…”
Section: Discussionmentioning
confidence: 99%
“…Some precedent for the existence of such long-lasting phylogenetic effects is provided by the existence of 'nocturnal' eye shapes in other diurnal amniote groups [10]. Some diurnal owls and diurnal geckos retain relatively large corneas compared with diurnal birds and lizards generally [7,9] (but see [51]). Similarly, both owls and geckos probably diversified as predominantly nocturnal radiations [52,53].…”
Section: Discussionmentioning
confidence: 99%
“…However, Hayes and Brooke (1990) have found that the Kerguelen petrel (Aphrodroma brevirostris) lacks a visual streak, but has a concentric distribution of the RGC density lines. Therefore, not only the 'openness' of the habitat, but also other factors like foraging strategy, prey capture technique, activity pattern and phylogenetic relatedness might influence the evolution of the RGC distribution in the retina (Hayes and Brooke, 1990;Lisney et al, 2012aLisney et al, ,b, 2013.…”
Section: Retinal Ganglion Cell Topographymentioning
confidence: 99%
“…For example, in an open terrain such as a savannah or the open ocean, all approaching objects are represented in a horizontal band on the retina (for a detailed explanation, see Hughes, 1977). Therefore, birds such as ostrich (Struthio camelus), little penguin (Eudyptula minor), king penguin (Aptenodytes patagonicus), and several species of owls (Strigiformes), waterfowl (Anseriformes: Anatidae) and procellariiform seabirds (Procellariiformes) have an elongated area of higher RGC density stretching across the retina called the visual streak (Hayes and Brooke, 1990;Boire et al, 2001;Coimbra et al, 2012;Lisney et al, 2012aLisney et al, , 2013. This conformation of RGCs allows them to see fine details at the horizon without moving the head or eyes (Hughes, 1977).…”
Section: Introductionmentioning
confidence: 99%
“…The retina was then washed in PBS and flattened on a gelatinized slide [Stone, 1981;Ullmann et al, 2012]. The pecten was removed prior to flattening to enable the retina to lie completely flat on the slide [Lisney et al, 2012[Lisney et al, , 2013. Additionally, this method minimized problems with asymmetric shrinkage across the retina [Ullmann et al, 2012] that could become prevalent if certain points of the retina remained partially adhered to the ora serrata or the area around the pecten.…”
Section: Retinal Ganglion Cell Density and Distributionmentioning
confidence: 99%
“…In general, species that hunt active prey, like falcons, hawks, owls, and flycatchers, have been reported to have higher cell densities in their retinal specializations (and in some cases more than one retinal specialization per retina) than species that feed on passive prey [e.g. Reymond, 1985Reymond, , 1987Coimbra et al, 2006Coimbra et al, , 2009Dolan and Fernández-Juricic, 2010;Fernández-Juricic et al, 2011a;Lisney et al, 2012]. Consequently, we predicted that American goldfinches would have a single fovea with a relatively low density of retinal ganglion cells compared to species which forage on active prey.…”
mentioning
confidence: 98%